Crab fishery of t h e Calicut coast with some aspects of t he population characteristics of Portunus sanguinolentus, P. pelagicus and Charybdis cruciata - Sarada, P T (Indian Journal of Fisheries, 2011)
Annual crab landings by mechanised trawlers ranged between 9.0 t (1988-’89) and 64.0 t (1987-’88). During 1987-’91 period. Portunus sanguinolentus (94.2 %), P. pelagicus (3.0 %) and Charybdis cruciata (2.8 %) were the dominant species. The carapace length-body weight relationship were : W = 0.01037 L^^"’ for P. sanguinolentus, W = 0.00374 L = ^^’^ â€¢’ for P. pelagicus and W= 0.00059 L ^^^’â€¢’’ for C. cruciata. The carapace width-body weight relationships of the respective species were : W = 0.00013 L ’’â€¢^"^^ W = 0.00024 Uâ„¢" and W = 0.00029 L ^ "’"*’’. The carapace length-carapace width relationships were W = 19.636+1.7218 L for P. Sanguinolentus, W = 13.6133 + 1. 9549 L for P. pelagicus and W = 0.9874 + 1. 5473 L for C. Cruciata. The size varied from 26-175 mm carapace with (C W) in P. sanguinolentus, 66-115 mm C W in P. pelagicus and 51-120 mm C W in C cruciata. In P. sanguinolentus a regular pattern of dominance of one sex over the other was absent. Maturity study indicated spawning throughout the year and the size at first maturity in female was 82.99 mm C.W. The L , K (annual) and t^ (annual) values were 172.9 mm C.W., 1.4939 and -0.0482 respectively in male. The respective values in female were 161.8 mm C.W., 1.574 and -0.0635. Introduction (